New strategy to increase sales in the post pandemic era (case of ivan gunawan cosmetics) - Soviasari, Maya; Dung Do, Anh (Enrichment : Journal of Management, 2024)
Ivan Gunawan Cosmetics (IGC), a local cosmetic brand established in 2017 and owned by a renowned Indonesian celebrity and fashion designer, experienced a sales decline during the pandemic. This study aims to identify challenges and propose authentic solutions for enhancing post-pandemic sales. Utilizing both qualitative and quantitative research, internal management interviews and loyal consumer feedback were collected through original questionnaires. Primary and secondary data were employed for a comprehensive analysis, integrating Porter's Five Forces, Value Chain Analysis, Competitor Analysis, SWOT, and Consumer Analysis. The proposed approach suggests adopting the Business Model Canvas as the foundational framework. The BMC encompasses product innovation, distribution expansion, revenue diversification, and improved customer relationships. Recognizing the competitive advantage of association with a public figure, must adeptly navigate heightened competition in both local and global markets with integrity. Chapter 5 offers concise recommendations for precise and authentic execution, including maintaining brand consistency, responsibly expanding distribution channels, and creating original, interactive, educational, and inspirational promotional content. As competition intensifies within the Indonesian cosmetic industry, the study underscores the pivotal role of authentically establishing a robust brand value and fostering genuine customer loyalty. Through survey methodologies, the research delves into an authentic analysis of consumer attitudes, incorporating original brand analysis variables and genuine consumer sentiments toward brand impressions.Implications of this research lie in the formulation of original marketing strategies for authentically fortifying post-pandemic sales, solidifying brand positioning with integrity, and genuinely nurturing customer loyalty amidst the competitive landscape, ensuring the sustained and ethically sound success of IGC's business.